English Teaching Methods - Irgasheva, Makhmuda (International Conference on Global Trends and Innovations in Multidisciplinary Research, 2026)
The article investigates current methods of teaching English as a second language through a study of how teaching methods developed from past to present and their applications in current educational settings. The analysis shows that successful English instruction needs teachers to use both conventional teaching methods and modern teaching methods while customizing their approach to meet the particular requirements and cultural background of their students.